Google® power tools bible - Coombs, Ted (Bible, 2007)
Get the most thorough and comprehensive guide to Google. Expand your world with the dozens of Google tools, applications, and services you'll find in this comprehensive book. Going well beyond the basics of search, this in-depth resource shows you ho.